Strategi Dakwah Islam Di Kalangan Masyarakat Muslim Minoritas Di Kecamatan Larantuka Kabupaten Flores Timur Provinsi Nusa Tenggara Timur - 10020220070, Shoharifal Laga Waja; Asep Ahmad Siddiq, Drs.,M.Si. (Bandung Conference Series: Islamic Broadcast Communication, 2025)
Larantuka District in East Flores is one of the Muslim minority areas in Indonesia. Dakwah activities in Larantuka certainly face various obstacles and the right da'wah strategy is needed. This research aims to identify effective Islamic da'wah strategies among Muslim minority communities in Larantuka District, East Flores Regency, East Nusa Tenggara and to find out the supporting and inhibiting factors for da'wah success. The research method used is qualitative with a descriptive approach. Data were collected through participatory observation, documentation, and in-depth interviews with religious leaders, community leaders, and the general public. The results of the research are inclusive and adaptive to the socio-cultural conditions of the local community. The applied da'wah strategy includes: (1) understanding the object of da'wah, (2) determination of da'wah material, (3) selection of da'wah methods, use of da'wah media, and evaluation of da'wah. Supporting factors for da'wah in Larantuka are in the form of social and community support, accommodating da'wah strategies, education and religious awareness, and government support. Factors inhibiting da'wah include: domination of minority communities, lack of human resources, economic factors and limited access, and cultural resistance. Efforts to overcome problems: strengthening the Muslim community, using media and technology, inclusive da'wah approaches, education and training, and good financial planning.